(untitled) (Revista Cerrados, 2017)
The Heike monogatari (the Tale of the Heike, fourteenth century) recounts the fall of the Heike, a military clan also known as Taira, at the end of the Genpei War (1180-1185). In it, there are features dozens of female characters. This essay examines the representation of a number of women of warrior backgrounds in the Heike monogatari. The aim is to present the sense of the world of the Heike women, their relationship with other characters, male and female, and their function in the story.